2016
DOI: 10.1186/s13033-016-0060-z
|View full text |Cite
|
Sign up to set email alerts
|

Promotion, prevention and protection: interventions at the population- and community-levels for mental, neurological and substance use disorders in low- and middle-income countries

Abstract: BackgroundIn addition to services within the health system, interventions at the population and community levels are also important for the promotion of mental health, primary prevention of mental, neurological and substance use (MNS) disorders, identification and case detection of MNS disorders; and to a lesser degree treatment, care and rehabilitation. This study aims to identify “best practice” and “good practice” interventions that can feasibly be delivered at these population- and community-levels in low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 120 publications
(109 reference statements)
3
67
0
Order By: Relevance
“…Also increasing awareness of chronic conditions via school-based programmes is considered a "good practice" strategy in LMICs. 316 Another system level approach would involve augmenting the competences of the existing work staff at all levels of care. Although education about the link between chronic physical and mental health conditions is an important tool to support changes in clinical practice, it is rarely a one-off solution to altering knowledge and behaviours.…”
Section: Innovations In Integration For Low-and Middle Income Countrimentioning
confidence: 99%
“…Also increasing awareness of chronic conditions via school-based programmes is considered a "good practice" strategy in LMICs. 316 Another system level approach would involve augmenting the competences of the existing work staff at all levels of care. Although education about the link between chronic physical and mental health conditions is an important tool to support changes in clinical practice, it is rarely a one-off solution to altering knowledge and behaviours.…”
Section: Innovations In Integration For Low-and Middle Income Countrimentioning
confidence: 99%
“…The bases for these wider types of intervention are sometimes called “platforms”, and two are particularly relevant here: population‐level and community‐level platforms. Examples of the former include legislation, regulations, and public information campaigns, and examples of the latter include schools, workplaces, and neighborhoods/community groups. A recent review, based upon the best available evidence from low‐ and middle‐income settings, has shown which such interventions are most cost‐effective.…”
Section: Community Services Provided Across Wider Platforms Of Carementioning
confidence: 99%
“…Trials conducted in low- and middle-income countries (LMICs) have demonstrated the efficacy and effectiveness of both psycho-pharmacological treatment and evidence-based psychotherapies for treating mental disorders [613]. Furthermore, studies on the cost-effectiveness of mental health treatments increasingly highlight the economic value of preventing and treating mental disorders in these settings [14••, 15]. …”
Section: Introductionmentioning
confidence: 99%